+0  
 
0
31
1
avatar

how to change the equation below into factored form f(x)=(x+14)^2-49

 Jan 29, 2019
 #1
avatar+95866 
+1

Let (x + 14) = a

Let 7 = b

 

So...we have

 

(x + 14)^2 - 7^2  =

 

a^2 - b^2  =

 

(a + b) ( a - b)   =

 

[ ( x + 14 ) + 7 ]  [ (x + 14) -  7 ]  =

 

[ x + 21 ] [ x + 7 ] 

 

 

cool cool cool

 Jan 29, 2019
edited by CPhill  Jan 29, 2019

11 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.